2004
DOI: 10.1086/383271
|View full text |Cite
|
Sign up to set email alerts
|

Medical Treatment of Diabetic Foot Infections

Abstract: Diabetic foot infections frequently cause morbidity, hospitalization, and amputations. Gram-positive cocci, especially staphylococci and also streptococci, are the predominant pathogens. Chronic or previously treated wounds often yield several microbes on culture, including gram-negative bacilli and anaerobes. Optimal culture specimens are wound tissue taken after debridement. Infection of a wound is defined clinically by the presence of purulent discharge or inflammation; systemic signs and symptoms are often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0
13

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(105 citation statements)
references
References 72 publications
2
90
0
13
Order By: Relevance
“…As noted in other studies [5,13], almost two-thirds of our patients with a foot infection were men, but men comprised just over one-half of the patients with non-foot infections. However, patients with a non-foot infection were more likely to have been recently hospitalised or to be residing in a skilled nursing facility, and were more severely ill on admission with higher rates of various physiological derangements.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As noted in other studies [5,13], almost two-thirds of our patients with a foot infection were men, but men comprised just over one-half of the patients with non-foot infections. However, patients with a non-foot infection were more likely to have been recently hospitalised or to be residing in a skilled nursing facility, and were more severely ill on admission with higher rates of various physiological derangements.…”
Section: Discussionsupporting
confidence: 79%
“…In the USA, about 111,000 persons with diabetes are hospitalised annually with foot infections and these precede and contribute to almost 60% of all lower extremity amputations [13]. Staphylococcus aureus is the most commonly isolated pathogen in SSTIs, both in ambulatory and hospitalised patients [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies used isotopes with a high radiation burden and low spatial resolution. Lipsky later suggested that a leucocyte scan might be useful in demonstrating that infection has been arrested [25]. We published in 2014 a paper suggesting that WBC-SPECT/CT could be used to predict DFO remission at the end of medical treatment with an optimal negative predictive value (100%) and that it could therefore be a very useful tool to guide the duration of antibiotic treatment in DFO [12].…”
Section: Discussionmentioning
confidence: 99%
“…16 Diabetic wounds show exacerbated inflammation and extensive necrosis often leading to amputation of the affected body parts. [17][18][19][20] Here, we hypothesized that TLR2 can specifically modulate inflammatory responses in cutaneous diabetic wounds and in part contributes to the impaired healing process. Our study results confirmed this hypothesis in two animal models of diabetic wounds, while also revealing that TLR2 is a key element in the induction of inflammation in the diabetic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of TLRs in the innate immune system and their potential role after tissue damage, we aimed to study how TLRs may be involved in the dysregulated inflammation observed in diabetic wounds. [17][18][19][20] Further, the inflammatory mechanisms involved in diabetic wounds have not been fully delineated. However, TLR2 expression, activation, and signaling are significantly increased in type 1 diabetes mellitus (T1DM) patients and nonobese diabetic (NOD) mice, and have been hypothesized to be significant in human health.…”
mentioning
confidence: 99%